Comment on and ldquo;Day and ndash;Care Surgery for Pilonidal Sinus Using Sinotomy Technique and Fibrin Glue Injection and rdquo; - Mehmet Ince; Erol Aslan (Archives of Clinical and Experimental Surgery, 2013)
[Arch Clin Exp Surg 2013; 2(2.000): 136-137]